Serious Adverse Events Reported with Dietary Supplement Use in the United States: A 2.5 Year Experience. (3rd March 2020) - Schmitz, Stephen M.; Lopez, Hector L.; Mackay, Douglas; Nguyen, Haiuyen; Miller, Paula E.
Abstract: Dietary supplement marketers assure the safety of their products by complying with current good manufacturing practices and a host of federal regulations, including those enforced by the Food and Drug Administration (FDA). Post-market surveillance is a key part of identifying safety problems associated with dietary supplement products. FDA requires dietary supplement marketers to provide a domestic address or phone number on product labels for consumers, family members, or health care professionals to report adverse events (AEs) associated with product use and to report all serious adverse events (SAEs) to the agency within 15 business days of receipt. We aimed to evaluate the characteristics of AEs reported with dietary supplement use, including dietary supplement type and Medical Dictionary for Regulatory Activities (MedDRA) system organ class (SOC) that occur with reported SAEs. A total of 41, 121 unique adverse event cases reported to two large, U.S.-based dietary supplement marketers in a 2.5-year period (March 1, 2014–August 31, 2016) were assessed for seriousness using established criteria. Each SAE was assigned one or more MedDRA preferred terms and system organ classes (SOC). The types of supplements most responsible for SAEs were assessed. Of the 41, 121 AE cases reported, 203 (0.48%) were SAEs. SAEs tended to occur with products marketed for weight loss (69.0%) and glycemic control (19.2%). SAEs occurred most commonly in the cardiovascular, gastrointestinal, and nervous system disorder SOCs. The percentage of SAEs reported to dietary supplement marketers is low, predominantly among consumers of two types of supplements. Further study is needed among a larger cohort of supplement users to determine causal associations between types of supplement products and serious adverse events.